IMPACT OF NPAS ON THE BANKS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Non-performing assets (NPAs) in the banking sector contribute to India's economy. No one should be surprised that banks drive economic growth in any economy. A thriving economy is great for banking and other financial institutions because it increases credit demand. Examining the development of the Indian economy over time, reveals that banks have been essential to the country's rapid economic growth. Banks and other financial institutions are expanding their product lines, geographic reach, and credit offerings. Non-performing loans are the most worrisome aspect of financial companies' rapid growth in recent years. Despite the long history of this issue, much research remains to be done. The Government of India and the Reserve Bank of India (RBI) have begun to deal with the growing number of non-performing loans; however, it will take a coordinated effort and a methodical strategy to solve the issue. Solving this problem requires hard work and an organised strategy.